THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMK ABDURRAB (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The objectives of this study were to perceive vocabulary mastery of students, reading comprehension of students, and whether there is a correlation between these two topics. The data were taken from 29 students in the second year at SMK Abdurrab. The tests were employed to quantify two variables, namely vocabulary mastery and reading comprehension. The statistical analyzes were performed with SPSS 25. The outcomes uncovered that students' vocabulary mastery and students' reading comprehension are at enough category. Meanwhile, the correlation analysis indicated on that point there is a positive correlation between vocabulary mastery (x) and reading comprehension (y). And when the Pearson value was interpreted based on correlation table is in the range 0.60 – 0.799, which means strong correlation.Key Words: Correlation, Vocabulary Mastery, Reading Comprehension